MEASUREMENT OF RESIDENTIAL SATISFACTION: ANALYSIS OF A BRAZILIAN METROPOLITAN REGION - Guimarães Junior, Djalma Silva; Sant’anna, Carlos Henrique Michels de; Saito, Michele Bezerra; Santos, Sérgio Pinheiro dos; Melo, Fagner José Coutinho de (Marketing & Tourism Review, 2021)
The housing sector in Brazil gained an impulse in the second half of the twentieth century with the creation of the housing funding system and a credit policy. However, the 1980s marked a period of crisis of the public debt and economic stagnation in the country, causing the dismantling of the housing policy and bringing the sector to a timid expansion phase through market mechanisms and individual initiatives. Since the beginning of 2000, new government programs have arisen for housing and the sector has boomed in the popular housing segment - subsidized by the government - and private market. However, an important factor in planning housing policy is the population’s satisfaction with their dwelling, little effort having been made to identify resident satisfaction level with their real estate, that is, to what extent the Brazilians are pleased with their housing and what the most important factors for the expansion of such satisfaction are. This survey uses data from 347 interviews conducted in the state of Pernambuco, Brazil, and proposes a logistic regression model to identify the factors that expand housing satisfaction. The following items were considered significant: bathroom space, residential ventilation, distance to parks and distance to religious centers.